Application and practice of trimodal prehabilitation model in preoperative management of patients with lung cancer undergoing video-assisted thoracoscopic surgery - Yao, Liping; Chen, Hui; Xue, Bei (Frontiers in Surgery, 2023)
The clinical treatment of lung cancer mainly adopts a comprehensive method, which is mainly surgical treatment, supplemented by radiotherapy or chemotherapy, and immunotherapy. Among them, video-assisted thoracoscopic surgery is the first choice for patients with NSCLC. At present, how to optimize perioperative management measures, optimize and improve the patient's body function, and promote postoperative rehabilitation are the hot spots of research by medical staff. In this study, 148 patients with lung cancer were selected as the research object, to analyze and discuss the application value of trimodal prehabilitation model in preoperative management of patients with lung cancer undergoing video-assisted thoracoscopic surgery.